PENGARUH FLIPBOOK LITERASI DAN NUMERASI TERHADAP HASIL AKM PESERTA DIDIK KELAS V DI SDN PLOSO WONOAYU - Lestari, Gritias Dwi; Aini, Nurul (JURNAL PENDIDIKAN DASAR, 2024)
Abstract: The aim of this research is to determine the effect of flipbooks on the AKM results of class V students at SDN Ploso Wonoayu for the 2023/2024 academic year with a research sample of 18 students. This research method is Quasi-experimental design using a One Group Pretest-Posttest Design. This design uses a set of limitations, namely an experimental group without a control group. The researcher's test data includes pretest and posttest multiple choice questions which include 20 literacy questions and 20 numeracy questions. The questions contained in it are related to literacy and numeracy questions obtained from a motivational application provided by the Ministry of Education and Culture which can only be accessed by students who take part in government programs such as teaching campuses so that researchers do not need to carry out validity and reliability tests, in order to obtain information on literacy and learning outcomes. numeracy which measures students' mastery of the material. To analyze the data using the normality test and paired sample t-test. By using literacy and numeracy flipbooks there is a significant influence on the AKM results of class V students from the pretest and posttest. The results of the paired sample t-test for literacy and numeracy have a significance level (2-tailed) 0.05 or 0.000 0.05 so we come to the conclusion that Hₒ is rejected and Ha is accepted. showed a significant increase. This shows that there are differences in literacy and numeracy pretest scores as well as literacy and numeracy posttest scores after using literacy and numeracy flipbooks at SDN Ploso Wonoayu.Keywords: Flipbook, Literacy and Numeracy, AKM Results                                                                                                         Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui pengaruh flipbook terhadap hasil AKM peserta didik kelas V SDN Ploso Wonoayu tahun ajaran 2023/2024 dengan sampel penelitian 18 peserta didik. Metode penelitian ini yaitu Quasi-experimental design dengan Menggunakan Rancangan One Group Pretest-Posttest Design. Rancangan ini menggunakan satu set batasan, yaitu kelompok eksperimen tanpa kelompok kontrol. Data tes peneliti meliputi pretest dan posttest soal pilihan ganda yang meliputi dari 20 soal literasi dan 20 soal numerasi. Soal yang tersusun didalamnya terkait soal literasi dan numerasi yang didapat dari aplikasi motivasi yang disediakan Kementerian Pendidikan dan Kebudayaan yang hanya bisa diakses oleh mahasiswa yang mengikuti program pemerintah seperti kampus mengajar sehingga peneliti tidak perlu melakukan uji validitas dan reliabilitas, guna mendapatkan informasi Hasil belajar literasi dan numerasi  yang mengukur penguasaan peserta didik terhadap materi. Untuk menganalisis data menggunakan uji normalitas dan uji paired sample t-test. Dengan menggunakan flipbook literasi dan numerasi terdapat pengaruh yang signifikan dari hasil AKM peserta didik kelas V dari pretest dan posttest. Hasil dari uji paired sample t-test literasi dan numerasi memiliki taraf signifikansi (2-tailed) 0,05 atau 0,000 0,05 sehingga kita sampai pada kesimpulannya bahwa Hₒ ditolak dan Ha diterima. menunjukkan peningkatan yang signifikan. Hal tersebut menunjukkan adanya perbedaan nilai pretest literasi dan numerasi serta nilai posttest literasi dan numerasi setelah di menggunakan flipbook literasi dan numerasi di SDN Ploso Wonoayu.Kata Kunci: Flipbook, Literasi dan Numerasi, Hasil AKM